PERAN PEMERINTAH DESA DALAM UPAYA MENSEJAHTERAKAN MASYARAKAT MELALUI WISATA WADUK PEDANG - Dian Wijaya (MAJAPAHIT POLICY, 2026)
The existence of the Pedang Reservoir indirectly brings changes to the village community. After successfully managing the Pedang Reservoir, the Tanjungan village government established a Village-Owned Enterprise (Bumdes). The first step after its establishment was to ensure that all vendors within the Pedang Reservoir area were operated by local Tanjungan residents. Not only were the vendors required to be local Tanjungan residents, but also the craftsmen and ticket attendants, all of whom were required to be local Tanjungan residents. This was to foster the local economy. After the Pedang Reservoir became a tourist attraction, many tourists came to visit, resulting in improved economic conditions for the Tanjungan community, leading to greater prosperity. This clearly contributes to the well-being of the Tanjungan village community, as the vendors, ticket attendants, parking attendants, and repairmen who repair any damage within the Pedang Reservoir area are all local Tanjungan residents.